2016
DOI: 10.1007/s10555-016-9618-0
|View full text |Cite
|
Sign up to set email alerts
|

Progression and metastasis of lung cancer

Abstract: Metastasis in lung cancer is a multifaceted process. In this review, we will dissect the process in several isolated steps such as angiogenesis, hypoxia, circulation, and establishment of a metastatic focus. In reality, several of these processes overlap and occur even simultaneously, but such a presentation would be unreadable. Metastasis requires cell migration toward higher oxygen tension, which is based on changing the structure of the cell (epithelial-mesenchymal transition), orientation within the stroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
340
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 437 publications
(357 citation statements)
references
References 126 publications
8
340
0
9
Order By: Relevance
“…Tumor-infiltrating CD45RO + memory cells correlate with favorable prognosis in patients with lung adenocarcinoma diagnosed cases are inoperable because of metastasis or present poor prognosis after surgery (4). Therefore, additional novel and convincing biological markers, which are helpful to indicate the diagnosis and prognosis for lung cancer, are urgently needed.…”
Section: Original Articlementioning
confidence: 99%
“…Tumor-infiltrating CD45RO + memory cells correlate with favorable prognosis in patients with lung adenocarcinoma diagnosed cases are inoperable because of metastasis or present poor prognosis after surgery (4). Therefore, additional novel and convincing biological markers, which are helpful to indicate the diagnosis and prognosis for lung cancer, are urgently needed.…”
Section: Original Articlementioning
confidence: 99%
“…In recent years, although radiotherapy, chemotherapy and surgery have been shown to effectively remove or reduce tumors, the ability to cure malignant tumors and prevent tumor metastasis and recurrence has been limited [3][4][5]. Studies have shown that the development of hepatocellular carcinoma may be related to HCSCs, which have the CSC characteristics of self-renewal and multi-directional differentiation, increasing the difficulty of liver cancer treatment [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…[73] Furthermore, cancer of unknown primary site accounts for 5-10% of diagnoses in Europe and the United States. [74] This is in line with early migration of carcinoma cells from the initial lesion and onset of metastasis early in the tumor development.…”
Section: Emtmentioning
confidence: 99%
“…[23] Whereas metastasis via the lymphatic route usually takes longer until distant metastases are set, spreading via blood vessels rapidly induces distant metastases. [73] Although it is stated that tumors release millions of cells per day, this estimation is based on a single experimental animal model which is no realistic representation of a human lesion. [47] Furthermore, the threshold of a poorer prognosis for colon, breast and prostate cancer patients with 3-5 CTCs/7.5 ml blood by the CellSearch© system point to a limited shedding of cells from such tumors.…”
Section: Detection Of Early Metastatic Diseasementioning
confidence: 99%